2011
DOI: 10.1186/1471-2466-11-33
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic mechanics of the murine lung after intratracheal bleomycin

Abstract: BackgroundDespite its widespread use in pulmonary fibrosis research, the bleomycin mouse model has not been thoroughly validated from a pulmonary functional standpoint using new technologies. Purpose of this study was to systematically assess the functional alterations induced in murine lungs by fibrogenic agent bleomycin and to compare the forced oscillation technique with quasi-static pressure-volume curves in mice following bleomycin exposure.MethodsSingle intratracheal injections of saline (50 μL) or bleom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 41 publications
8
62
1
3
Order By: Relevance
“…Concordant with earlier reports (49,50), the collagen deposition and distribution pattern was primarily bronchocentric. Exacerbated pulmonary fibrosis in BLM-treated EC-ATG7 Ϫ/Ϫ mice was further associated with increased TGF␤1 expression and activity along with up-regulation of ␣SMA and TGF␤-responsive CTGF expression (Fig.…”
Section: Days After Blm Instillation In the Ec-atg7supporting
confidence: 91%
“…Concordant with earlier reports (49,50), the collagen deposition and distribution pattern was primarily bronchocentric. Exacerbated pulmonary fibrosis in BLM-treated EC-ATG7 Ϫ/Ϫ mice was further associated with increased TGF␤1 expression and activity along with up-regulation of ␣SMA and TGF␤-responsive CTGF expression (Fig.…”
Section: Days After Blm Instillation In the Ec-atg7supporting
confidence: 91%
“…Some studies suggested that hyperoxia increased compliance as in the case of emphysematous lungs, whereas other studies concluded hyperoxia decreased compliance because the lungs are less pliable (47)(48)(49)(50). We tested murine pulmonary outcomes at 6 weeks in accordance with previous studies (36,47,49).…”
Section: Discussionmentioning
confidence: 99%
“…These changes in lung structure lead to a severe impairment of lung function related to a decreased elasticity. Indeed, increased lung elastance as well as decreased compliance (the reciprocal of elastance) have been shown in humans (19,26,38) and in small rodent pulmonary fibrosis models (1,7,12,15,30,53,57,58). Moreover, changes in tidal volume and breathing cycle times have been shown in a mouse fibrosis model (33).…”
mentioning
confidence: 99%
“…Although the pathway of remodeling during fibrotic processes is still not completely understood, it is so far known that the lung structure is altered by loss of alveolar surface area, secondary to alveolar epithelial cell injury, and loss of lung elasticity, secondary to interstitial inflammation, proliferation/ migration of fibroblasts, and deposition of extracellular matrix, primary collagen, and proteoglycans (14,15,23,30,39,57,59). These changes in lung structure lead to a severe impairment of lung function related to a decreased elasticity.…”
mentioning
confidence: 99%